Seroprevalence of Avian Influenza in Guinea Fowls in Some Districts in the Upper East Region of Ghana - Albert Agyapong Tweneboah; Sherry Ama Mawuko Johnson; Patrick Mensah Amponsah; Derrick Adu Asare; Benjamin Obukowho Emikpe (Veterinary Medicine and Science)
ABSTRACT The guinea fowl (Numida meleagris) holds significant agricultural importance in Ghana, particularly in the Northern, Upper East and Upper West Regions. Despite their economic and cultural significance, guinea fowls face a potential threat from avian influenza, a global concern for its adverse impact on poultry populations. This study assessed the seroprevalence of the virus in mature guinea fowls in the Upper East Region. A cross‐sectional survey was conducted in three districts within the Upper East Region from April to June 2023. Blood samples were collected from 397 guinea fowls that are over 4 weeks old, and seroprevalence was determined using ID Screen Influenza A Antibody Competition Enzyme‐linked immunosorbent assay (ELISA). The study analysed demographic factors such as sex, age and source of birds, employing statistical methods to establish associations. Among the sampled guinea fowls, 24.7% tested positive for avian influenza antibodies, whereas 75.3% were seronegative. Age did not show statistically significant associations with seroprevalence, but intriguing patterns were observed. Adult guinea fowls exhibited higher seroprevalence (23.7%) compared to growers (1.0%). The source of birds showed no significant association, but birds from slaughter points demonstrated higher seroprevalence (11.6%) compared to households (5.0%) and live bird markets (8.1%). In conclusion, the study underscores the importance of monitoring avian influenza in guinea fowls to implement effective control measures. The presence of antibodies suggests guinea fowls may contribute to virus transmission in the Upper East Region. The study recommends ongoing nationwide surveillance to assess the true prevalence of avian influenza in guinea fowls across Ghana.